Propionic Acidemia: Diagnosis and Neuroimaging Findings of This Neurometabolic Disorder - KARIMZADEH, Parvaneh; JAFARI, Narjes; AHMAD ABADI, Farzad; JABBEHDARI, Sayena; TAGHDIRI, Mohammad-Mahdi; ALAEE, Mohammad-Reza; GHOFRANI, Mohammad; TONEKABONI, Seyed Hassan; NEJAD BIGLARI*, Habibeh (Iranian Journal of Child Neurology, 2014)
How to Cite This Article: Karimzadeh P, Jafari N, Ahmad Abadi F, Jabbehdari S, Taghdiri MM, Alaee MR, Ghofrani M, Tonekaboni SH, Nejad Biglari H. Propionic Acidemia: Diagnosis and Neuroimaging Findings of This Neurometabolic Disorder. Iran J Child Neurol. 2014 Winter; 8(1):58-61. Objective Propionic acidemia is one of the rare congenital neurometabolic disorders with autosomal recessive inheritance. This disorder is caused by a defect in the propionyl-CoA carboxylase enzyme and can be presented with life-threatening ketoacidosis, lethargy, failure to thrive, and developmental delay. Materials & Methods The patients diagnosed as having propionic acidemia in Neurology Department of Mofid Children’s Hospital in Tehran, Iran, between 2002 and 2012 were include in our study. This disorder was confirmed by clinical manifestations, neuroimaging findings, and neurometabolic assessment in the reference laboratory in Germany. Our study was conducted to define the sex, age, gender, past medical history, developmental status, clinical findings, and neuroimaging manifestations in 10 patients with propionic acidemia. Results Seventy percent of patients were offspring of consanguineous marriages. In this study, only one patient had microcephaly at birth, but at detection time, 30% of patients had head circumference and weight below the 3rd percentile. The patients were followed for approximately 5 years and this follow-up showed that the patients with early diagnosis had a more favorable clinical response. Neuroimaging findings included brain atrophy, white matter and globus pallidus involvement. Conclusion Finally we suggest that early diagnosis and treatment have an important role in the prevention of disease progression. References: Ramachandran R, Pietz J. Propionic acidemia without acidemia: a case report. J Perinatol 1995;15(1):71-3. Figueras Aloy J, Ribes Rubio A, Vilaseca Busca MA, Lluch Mir M, Brines Godino P, Jiménez González R, et al. [The neonatal form of propionic acidemia]. An Esp Pediatr 1988;29(6):459-62. Yuan L. [Propionic acidemia: one case report]. Zhongguo Yi Xue Ke Xue Yuan Xue Bao 1991;13(2):141-3. Hsu WC, Lin SP, Huang FY, Wang PA, Hsiao KJ. [Propionic acidemia: report of a case that is successfully managed by peritoneal dialysis and sodium benzoate therapy]. Zhonghua Yi Xue Za Zhi (Taipei) 1990;46(5):306-10. Schreiber J, Chapman KA, Summar ML, Ah Mew N, Sutton VR, MacLeod E, et al. Neurologic considerations in propionic acidemia. Mol Genet Metab 2012;105(1):10-5. Chapman KA, Gropman A, MacLeod E, Stagni K, Summar ML, Ueda K, et al. Acute management of propionic acidemia. Mol Genet Metab 2012;105(1):16-25. Ryu J, Shin YH, Ko JS, Gwak MS, Kim GS.Intractable metabolic acidosis in a child with propionic academia undergoing liver transplantation -a case report. Korean J Anesthesiol 2013;65(3):257-61. Fernandes J, Saudubray JM, Berghe GVD, Walter JH. Inborn Metabolic Diseases. 4th ed. Berlin: Springer;2006. P.247–256. Sutton VR, Chapman KA, Gropman AL, MacLeod E, Stagni K, Summar ML, et al. Chronic management and health supervision of individuals with propionic acidemia. Mol Genet Metab 2012;105(1):26-33. Lehnert W, Sperl W, Suormala T, Baumgartner ER. Propionic acidaemia: clinical, biochemical and therapeutic aspects. Experience in 30 patients. Eur J Pediatr 1994;153(7 Suppl. 1):S68–S80. Ozand PT, Rashed M, Gascon GG, Youssef NG, Harfi H, Rahbeeni Z, et al. Unusual presentations of propionic acidemia. Brain Dev 1994;16(Suppl):46-57. Feliz B, Witt DR, Harris BT. Propionic acidemia: a neuropathology case report and review of prior cases. Arch Pathol Lab Med 2003;127(8):e325-8. Hamilton RL, Haas RH, Nyhan WL, Powell HC, Grafe MR. Neuropathology of propionic acidemia: a report of two patients with basal ganglia lesions. J Child Neurol 1995;10:25-30. Brismar J, Ozand PT. CT and MR of the brain in disorders of the propionate and methylmalonate metabolism. Am J Neuroradiol 1994;15(8):1459-73. Bergman AJ, Van der Knaap MS, Smeitink JA, Duran M, Dorland L, Valk J, et al. Magnetic resonance imaging and spectroscopy of the brain in propionic acidemia: clinical and biochemical considerations. Pediatr Res 1996;40(3):404-9.